2021
DOI: 10.3390/ijms22020834
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diets with Differential Fatty Acids Induce Obesity and Perturb Gut Microbiota in Honey Bee

Abstract: HFD (high-fat diet) induces obesity and metabolic disorders, which is associated with the alteration in gut microbiota profiles. However, the underlying molecular mechanisms of the processes are poorly understood. In this study, we used the simple model organism honey bee to explore how different amounts and types of dietary fats affect the host metabolism and the gut microbiota. Excess dietary fat, especially palm oil, elicited higher weight gain, lower survival rates, hyperglycemic, and fat accumulation in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 63 publications
2
21
1
3
Order By: Relevance
“…They strongly impacted the bees' gut microbiota, with high-fat diets, e.g. increasing the relative abundance of Gilliamella and decreasing levels of Bartonella [30]. Our results did not confirm this pattern for those two bacterial genera, likely because they were in general only marginally detectable in our solitary bee system.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…They strongly impacted the bees' gut microbiota, with high-fat diets, e.g. increasing the relative abundance of Gilliamella and decreasing levels of Bartonella [30]. Our results did not confirm this pattern for those two bacterial genera, likely because they were in general only marginally detectable in our solitary bee system.…”
Section: Discussioncontrasting
confidence: 72%
“…At the same time, polyunsaturated fatty acids (PUFAs), and more precisely the ratio of omega 6 : 3 fatty acids, are important for cognitive abilities in honeybees [73,113,114]. In fact, a recent study found that dietary fatty acid profiles do not only impact bee longevity, but also their lipid metabolism and immune-related gene expression [30]. They strongly impacted the bees’ gut microbiota, with high-fat diets, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…play a protective role against polystyrene microplastics exposure by stimulating the expression of antioxidative CAT, detoxification CYPQ1 and GSTS3, and immune system-related Domeless, Hopscotch, and Symplekin genes in the midgut. 443 In the gut of honey bees, Lactobacillus species of L. plantarum (strains H28, H24, KX519413, KX519414, LP8, LP25, LP86, LP95, LP100) and L. kunkeei were characterized by an increased antioxidant potential that protects against different pesticides. 436,440,[444][445][446] All of these strains of lactobacteria from the gut of honey bees with an increased antioxidant potential can be selected as perspective strains for creating pharmabiotics.…”
Section: Perspectivesmentioning
confidence: 99%
“…in the microbiome increased significantly, while the rate of Bartonella sp. decreased (Wang et al, 2021).…”
Section: Factors Affecting Honey Bee Microbiotamentioning
confidence: 97%